Rethinking Evolutionary Psychology - Goldfinch, A. author. aut Link
VII, 218 p.
Keywords: Rethinking Evolutionary Psychology identifies, champions and vindicates a streamlined evolutionary psychology. It offers a new way of thinking that moves decisively away from theoretical and critical excess. Where standard accounts often obscure and distort, this book emphasizes and develops evolutionary psychology's heuristic credentials.